2017
DOI: 10.1093/gerona/glx129
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations Between Walking Speed and Amount of Self-reported Time Spent Walking Over a 9-Year Period in Older Women and Men

Abstract: The results suggest declining walking speed as a precursor to declining engagement in physical activity, but the converse association was not evident. Improving walking speed may be a method to increase physical activity among elderly individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 27 publications
3
14
0
Order By: Relevance
“…These findings validate previous results [23], by demonstrating the relationship persists in a less highly selected, more representative sample of older adults, and when PF and PA measures are collected annually as opposed to every 4-5 years. Other studies examining the relationships between PA and PF, in older adults, have yielded mixed results.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These findings validate previous results [23], by demonstrating the relationship persists in a less highly selected, more representative sample of older adults, and when PF and PA measures are collected annually as opposed to every 4-5 years. Other studies examining the relationships between PA and PF, in older adults, have yielded mixed results.…”
Section: Discussionsupporting
confidence: 87%
“…A secondary analytic approach was specified a priori; the goal of this analysis was to, as closely as possible, match the analytic approach used in our previous work, which contained three-time points of PF and PA [23], to determine if results were consistent. This approach estimated raw PA and PF change scores, using only data from cycles 1, 5 and 9, to define 'early change' (cycles 5-1) and 'late change' (cycles 9-5).…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…On average, older adults sleep for a short duration, have more fragmented sleep, and have altered sleep architecture in comparison to younger adults (Scullin & Bliwise, ). Older adults also engage in fewer minutes of overall PA (Barnett, Sluijs, Ogilvie, & Wareham, ) and walk less often (Best et al, ). Such changes might negatively impact subsequent health.…”
Section: Introductionmentioning
confidence: 99%
“…In older men, gait speed and grip strength have been associated with MVPA ( 24 ). A recent longitudinal analysis identified gait speed to be predictive of change in amount of walking, independent of grip strength ( 25 ). In the present study, an independent influence of gait speed was observed, but not grip strength.…”
Section: Discussionmentioning
confidence: 99%